National Football League scouting combine test results of elite-level National Football League players - LaPlaca, D. A.; McCullick, B. A. (Research Quarterly for Exercise and Sport, 2025)
This study aimed to determine elite and poor performance for each offensive and defensive position group on every physical test performed at the NFL Scouting Combine Descriptive statistics were calculated as well as independent samples t-tests for the 15 position groups relative to their performance in the NFL Scouting Combine tests, including: (a) 40-yard Dash, (b) Vertical Jump, (c) Bench Press, (d) Broad Jump, (e) Three-cone Drill, and (f) Shuttle Run. Each player`s height and weight were also analyzed. The 15 position groups include Quarterbacks (n = 206), Fullbacks (n = 64), Running Backs (n = 314), Wide Receivers (n = 501), Tight Ends (n = 187), Offensive Tackles (n = 279), Guards (n = 198), Centers (n = 99), Cornerbacks (n = 374), Free Safeties (n = 132), Strong Safeties (n = 129), Outside Linebackers (n = 273), Inside Linebackers (n = 162), Defensive Ends (n = 280), and Defensive Tackles (n = 273). For each of the 15 position groups, there was at least one NFL Scouting Combine test result that had a statistically significant difference at the p < .05 or p < .001 level when comparing players who averaged playing in at least 10 games per season versus those that played in less than 10 games. The results of this study provide knowledge of which physical test is essential for each offensive and defensive position and can be helpful for those charged with making player personnel decisions in NFL organizations.